COMPARATIVE EVALUATION OF THE PHARMACOPEY REQUIREMENTS FOR MEDICINAL PLANT RAW MATERIALS CONTAINING CARDIAC GLYCOSIDES (Experimental biology, 2022)
Proper assessment of the quality of the obtained phytosubstances from the raw materials under study involves establishing the level of requirements for its quality. In this regard, the aim of the work is to establish the pharmacopoeial level of requirements for the quality of medicinal plant raw materials containing cardiac glycosides, based on the results of a comparative evaluation of pharmacopoeial monographs.16 pharmacopoeias were used to collect data, of which 4 were homeopathic. The search was performed according to the keywords denoting the names of cardiac glycosides and pharmacopoeia types of medicinal plant raw materials in Latin and the language of pharmacopoeia.Based on the comparative analysis, the main list of quality indicators has been established, taking into account the requirements of national standards, which include: definition; identification, including macro- and microscopy, physico-chemical methods for determining biologically active substances; tests that include the determination of foreign impurities, weight loss during drying, the content of total ash, ash insoluble in hydrochloric acid; quantitative determination; microbiological purity; radionuclides, heavy metals, storage conditions and shelf life.Thus, unified requirements for the quality of medicinal plant raw materials containing cardiac glycosides have been developed, and optimal regulated norms for the main quality indicators have been determined, and their relationship with the quantitative content of cardiac glycosides in raw materials has been established.